Sustainable Architecture in Pakistan: A Path to LEED Certification: An Architect’s Perspective - Kashif Riaz; Umer Mahboob Malik; Aksam Qureshi; Zahid Ramzan; Faizan Saeed; Naveed Rehman; Sarfraz Ahmed (Spectrum of Engineering Sciences, 2024)
This paper explores the sustainable architecture practices worldwide and in Pakistan in the context of adopting these practices and pursue LEED certification. This paper by studying various published papers investigates the methodologies by which architects, construction professionals and other stakeholders can build environment, following LEED standards, exploring the value of renewable materials, energy conservation systems, that are adoptable to local cultural and historical context. This paper highlights the challenges presented due to climate change, natural resource depletion, and traditional construction practices, and explores avenues for innovation and sustainable growth. This research paper by adopting qualitative research method, explores various papers and examining LEED principles and criteria, offers perspectives on the current state of sustainable architecture in Pakistan, challenges and opportunities being faced, and proposes strategies for further developments. Key words: Sustainable Architecture, sustainable construction, Pakistan, LEED Certification, Green Building, Energy Efficiency, Urban Development, Green Building Practices, Innovation